(untitled) (Informatica, 2021)
The geographically distributed feedback control loops connected via communication network elucidate the core of networked control system (NCS), wherein different users spread all over the world can regulate, direct and command the components of control system located at distant location. The proficiency of NCS provides sceptre to its user and multifaceted assignments are successfully endowed through it. The ascendancy of NCS is lowered through inconspicuous delays which destabilize the system. The induction of delays in the network lead to the proscription of packet delivery, bandwidth utilization and stable system response. In this manuscript Smith predictor is modified using Markov approach and Kalman estimation algorithm. The scheme has been implemented by using Matlab/ Simulink software for delay compensation. Performance analysis shows the robustness of modified Smith-Predictor controller in comparison to classical Smith predictor controller and proportional-integral-derivative based controllers.